Small and Medium Enterprises Halal Literacy Measurement During Covid-19 Pandemic - Helma Malini (Journal of Islamic Economics and Finance Studies, 2021)
AbstractThe purpose of this study is to determine the level of halal literacy among Small and Medium Enterprises (SMEs) in Indonesia. The aspects studied are knowledge about halal behavior, halal attitude and halal knowledge. This research is a descriptive study based on a survey of research subjects using a purposive sampling technique. The population in this study were SMEs in Indonesia with a focus on the cities of Jakarta, Bandung, Surabaya and Pontianak with a total sample of 150 people. The sample was composed of owners of SMEs in Indonesia between the ages of 19 and 45. The age group used as a sampling criterion is determined by the differences that may exist between age groups or generations. The results of the study indicate that the overall level of education in Indonesia, SMEs halal literacy is defined as sufficient literacy. It is hoped that the proposed measures of halal literacy in SMEs will assist policymakers in better understanding the level of literacy among SMEs to create a better halal ecosystem to improve economic resilience’s toward crisis. AbstrakTujuan dari penelitian ini adalah untuk mengetahui tingkat literasi halal pada Usaha Kecil Menengah (UKM) di Indonesia. Aspek yang dipelajari adalah pengetahuan tentang perilaku halal, sikap halal dan pengetahuan halal. Penelitian ini merupakan penelitian deskriptif berdasarkan survei terhadap subjek penelitian dengan menggunakan teknik purposive sampling. Populasi dalam penelitian ini adalah UKM di Indonesia dengan fokus kota Jakarta, Bandung, Surabaya dan Pontianak dengan jumlah sampel 150 orang. Sampel terdiri dari pemilik UKM di Indonesia antara usia 19 dan 45 tahun. Kelompok usia yang digunakan sebagai kriteria pengambilan sampel ditentukan oleh perbedaan yang mungkin ada antara kelompok usia atau generasi. Hasil penelitian menunjukkan bahwa secara keseluruhan tingkat pendidikan di Indonesia, literasi halal UKM didefinisikan sebagai literasi yang cukup. Diharapkan langkah-langkah literasi halal yang diusulkan di UKM akan membantu pembuat kebijakan dalam lebih memahami tingkat literasi di kalangan UKM untuk menciptakan ekosistem halal yang lebih baik untuk meningkatkan ketahanan ekonomi terhadap krisis.